Comparative pathology of experimental infection with four isolates of Trypanosoma evansi in Wistar albino Rats - KRISHNAMOORTHY, P; SENGUPTA, P P; ROY, PARIMAL (The Indian Journal of Animal Sciences, 2021)
In the present study, pathological changes due to experimental infection with four isolates of T. evansi were studied in rats to know the pathogenicity. Male Wistar albino rats (140) were divided in five groups of 28 rats each (4 isolate groups and 1 control group). Each rat was infected with 1×105 T. evansi from buffalo, dog, leopard and lion isolates and normal saline in control group by intraperitoneal route. Four rats were sacrificed on Day 1 (D1) to D7 post infection in each group and collected blood was for microscopic examination and tissues for pathology. Blood smear examination revealed presence of trypanosomes on D3, D4, D5 and D5 in buffalo, dog, leopard and lion isolates, respectively. All the T. evansi infected rats showed hypoglycaemia and increased blood urea nitrogen in serum. Rats showed clinical signs with dullness, lethargy and hunched back on D7. Liver showed vacuolar degeneration, congestion of blood vessels and infiltration of mononuclear cells on D7 in buffalo, dog, lion isolates, and no changes in leopard isolate infected rats. Kidney, spleen, lung and testis revealed pathological changes in buffalo and dog isolates. Trypanosomes were present in the endocardium of heart in buffalo isolate infected rats. Immunohistopathology revealed presence of trypanosome antigens in the blood vessels of liver, and spleen. Thus, based on trypanosome counts, serum glucose, blood urea nitrogen and pathological changes, there was variation between these isolates and revealed pathogenicity in ascending order as leopard, lion, dog and buffalo isolates in rats.